Salicylic Acid Improves Morpho-Physiological Traits and Biomass of Kale under Drought Stress - Rosyida Rosyida; Arina Dinana; Karno Karno; Muhaimin Ar Rasyid; Fajrin Pramana Putra; Nur Izzatul Maulidah (Universitas Panji Sakti, 2026)
Drought stress in agricultural land disrupts the physiological processes, growth, and yield of kale (Brassica oleracea L. var. acephala). This study evaluated the physiological responses, growth, and yield of kale treated with salicylic acid, a potential strategy to enhance plant tolerance to drought stress, in a greenhouse at the Department of Agriculture, Universitas Diponegoro, Semarang. A 4 × 4 factorial experiment was arranged in a Completely Randomized Design (CRD) with three replications. The first factor was drought level (100%, 80%, 60%, and 40% field capacity). The second factor was salicylic acid (SA) concentration 0, 0.75, 1.5, and 2.25 mM). The results indicated that physiological responses (chlorophyll a, chlorophyll b, total chlorophyll, relative water content, and electrolyte leakage) remained largely stable under moderate drought stress (60% FC), whereas plant growth parameters (plant height, leaf number, and leaf area) were reduced by 14.5–20.7% compared with the control (100% FC). At 40% FC, both physiological and growth responses were more severely affected; electrolyte leakage increased markedly, and plant height, leaf area, and dry biomass weight decreased by 24.4%, 47.2%, and 60.5%, respectively, compared with the control (P < 0.05). The best treatment was the application of 1.5 mM salicylic acid, which increased the relative water content by 4.13% and decreased the electrolyte leakage by 34.70% compared to untreated plants (P < 0.05). This concentration was likely more effective due to optimal stomatal regulation, increased antioxidant enzyme activity, and maintained membrane integrity, indicating that 1.5 mM SA has potential as a biostimulant to improve kale water status and membrane stability. However, field validation across locations and seasons is needed before recommending it for dryland farming.